Navigating the Digital Shift: The State of Junior High Schools' Technological Readiness in Indonesia - Kistanti, Aisyah; Sunardi; Drajati, Nur Arifah (VELES Voices of English Language Education Society, 2024)
The digital shift in education requires readiness among school members to manage the challenges of organizational change. This study investigates the technological readiness of junior high schools in Indonesia from teachers' perspective, using Weiner's (2009) theory of organizational readiness for change, and examines students' readiness for digital learning. Participants included teachers and students from four junior high schools in Boyolali, Central Java, selected through convenience sampling with a 95% confidence level (0.05). Descriptive statistical analysis indicated a positive readiness for digital transformation (mean = 3.74). The study found that only the Valence of Change factor had a statistically significant correlation with schools' readiness for digital shift. Furthermore, respondents showed a positive attitude toward digital learning, with no significant gender differences in students' perceptions and use of digital tools. These findings offer valuable insights for educators, researchers, and school administrators in driving digital transformation in education. The study recommends integrating digital learning into the curriculum to boost student engagement and interest.